Quality inspection system for canned pineapple - Nam, Zhen Kai (2010)
The color image processing plays an important role in many of the applications nowadays. The variety image processing technique and the excellent performance is enhancing the human life to become more qualitative. This Quality Inspection System is mainly concern on the software development with MATLAB. The Quality Inspection System is helping LPNM to verify the quality of the cans of pineapple of the factory. It is more to manage quality control and health regulation at registered pineapple factory. The cans of pineapple will pick randomly to do the quality test. This system will scan and detect the yellowish of the pineapple in the cans via camera. The system will pass and certify only if the yellowish of the pineapple pass the standard of LPNM. After pass through all the testing, LPNM will certify and allow the cans of pineapple export to other countries. Through the final year project, it can be concluded that image processing technique can be implemented to detect grades for canned pineapple. The Quality Inspection System able to display the grades through a pop up window